Formulasi dan Uji Aktivitas Antibakteri Sediaan Sabun Mandi Padat Kombinasi Ekstrak Daun Sirih Hijau (Piper betle L.) dan Daun Kemangi Lombok (Ocimum sanctum L.) terhadap Bakteri Propionibacterium acnes. - Liana Oktavia Cahyani; Rosnalia Widyan; Wulan Ratia Ratulangi; Mohd Nazil Salleh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Acne is one of the most common skin disorders caused by Propionibacterium acnes, while prolonged use of antibiotics may contribute to bacterial resistance, highlighting the need for natural antibacterial alternatives. This study aimed to formulate solid bath soap containing a combination of green betel leaf (Piper betle L.) and Lombok basil (Ocimum sanctum L.) extracts and to evaluate its physical characteristics and antibacterial activity against Propionibacterium acnes. A laboratory experimental method was employed using three extract concentrations, namely 5%, 7%, and 9%. The evaluation included organoleptic properties, homogeneity, pH, moisture content, foam height, irritation test, antibacterial activity, and statistical analysis using One Way ANOVA followed by Tukey HSD. The results demonstrated that all formulations fulfilled the physical quality requirements, caused no skin irritation, and exhibited antibacterial activity. The average inhibition zones were 19.0 mm, 25.6 mm, and 28.6 mm, while the positive control produced a 29.0 mm inhibition zone. Statistical analysis revealed a significant difference in antibacterial activity among treatments (p=0.010). These findings indicate that increasing extract concentration enhanced antibacterial activity, although differences among formulations were not entirely significant. Therefore, the combination of green betel leaf and Lombok basil extracts has promising potential as a natural active ingredient in antibacterial solid bath soap for inhibiting the growth of Propionibacterium acnes.